PHYSICO–CHEMICAL PROPERTIES OF PROTEIN PREPARATIONS - Świtalski, Maciej; Ruszkowska, Millena (The journal of contemporary issues in business and government, 2021)
The analysis of cohesiveness and flowing properties is based on the determination of the physicochemical properties of powdered food. The research material of the study consisted of 7 types of protein preparations. The protein supplements were analysed in terms of: water activity and water content, bulk density, static angle of repose (cone angle) wettability and kinetic angle of repose in order to determine initially their suitability for transport on the production line. The products were differentiated by water content and activity. The highest level of these parameters was observed in organic pumpkin protein what resulted in reduction of bulk density of the product. The performed determinations indicated mostly intermediate cohesiveness and at most fair flowability of the majority of the tested powdered protein supplements. All preparations, with the exception of pumpkin and brown rice products, had poor wettability. Some of the preparations especially beef protein isolate may cause flow obstructions.